Dysregulation of metabolites and high-altitude illnesses development under plateau conditions - Bai, Xue; Qi, Yujuan; Zhang, Qiang (Frontiers in Physiology, 2025)
BackgroundUnder plateau conditions, changes in metabolite levels can affect cellular signal transduction, protein activity, and gene expression, thereby inducing a series of physiopathological changes. Altered metabolite signaling in plateau environments may be associated with the onset and progression of high-altitude illnesses. This review summarizes the effects of a plateau environment on diseases, the mechanism of occurrence of such high-altitude illnesses, and the regulation of diseases by metabolites and proposes the role of metabolites in regulating high-altitude illnesses in plateau environments.Main bodyThrough a systematic review and analysis of the existing literature, we propose and focus on an original theoretical framework for the metabolic regulation of high-altitude illnesses. We hypothesize that the development of high-altitude illnesses is not merely a reflection of passive changes in metabolites but rather stems from an imbalance in a recognizable and intervenable metabolic regulatory network.ConclusionMetabolites have very important roles and implications in high-altitude illnesses, and a better comprehension of the regulatory role of metabolites in the pathogenesis of high-altitude illnesses can provide theoretical support for the prevention and treatment of high-altitude illnesses.